Reconstructing the population activity of olfactory output neurons that innervate identifiable processing units - Namiki, Shigehiro; Kanzaki, Ryohei (Frontiers in Neural Circuits, 2008)
We investigated the functional organization of the moth antennal lobe (<abbrev>AL</abbrev>), the primary olfactory network, by integrating single-cell electrophysiological recording data with geometrical information. The moth AL contains about 60 processing units called glomeruli that are identifiable from one animal to another. We were able to monitor the output information of the <abbrev>AL</abbrev> by recording the activity of a population of output neurons, each of which innervated a single glomerulus. Using compiled in vivo intracellular recordings and staining data from different animals, we mapped the odor-evoked dynamics on a digital atlas of the <abbrev>AL</abbrev> and geometrically reconstructed the population activity. We examined the quantitative relationship between the similarity of olfactory responses and the anatomical distance between glomeruli. Globally, the olfactory response profile was independent of the anatomical distance, although some local features were present. Olfactory response profiles of superficial glomeruli were approximately similar, whereas those of deep glomeruli were different with each other, suggesting network architectures are different in superficial and deep glomerular networks during olfactory processing.